A case–control study of self-reported health, quality-of-life and general functioning among recent immigrants and age- and sex-matched Swedish-born controls. Issue 8 (December 2014) - Löfvander, Monica; Rosenblad, Andreas; Wiklund, Tony; Bennström, Halina; Leppert, Jerzy
Aim: To examine whether new immigrants had inferior quality-of-life, well-being and general functioning compared with Swedish age- and sex-matched controls. Methods : A prospective case–control study was designed including immigrants from non-European countries, 18–65 years of age, with recent Permanent Permits to Stay (PPS) in Sweden, and age- and sex-matched Swedish-born (SB) persons from the general population in Västmanland County, Sweden. The General Health Questionnaire (GHQ-12), the brief version of the World Health Organization Quality-of-Life (WHOQOL-BREF) Scale and the General Activity Functioning Assessment Scale (GAF) from DSM-IV were posted (SB), or applied in personal interviews (PPS) with interpreters. Differences between the PPS and SB groups were measured using McNemar's test and Wilcoxon signed-rank test conducted separately for observations at baseline, 6- and 12-month follow-up. Results : There were 93 pairs (mean age 36 years). Persons from Somalia (67%) and Iraq (27%) dominated the PPS group. The differences between the groups were statistically significant for all time points for the Psychological health and Social relationship domains of WHOQOL-BREF, and for the baseline and 6-month follow-up time points of GHQ-12 where the PPS-group had a higher degree of well-being, health and quality-of-life than the SB. This tendency applied for both sexes in the immigrant group. Conclusions : These new immigrants did not have inferior physical or psychological health, quality-of-life, well-being or social functioning compared with their age- and sex-matched Swedish born pairs during a 1-year follow-up. Thus, there is reason to advocate immigrants' fast integration into society.